2007
DOI: 10.1016/j.ejheart.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial enlargement and NT‐proBNP as predictors of sudden cardiac death in patients with heart failure

Abstract: Aims: The identification of valuable markers of sudden cardiac death (SCD) in patients with established HF remains a challenge. We sought to assess the value of clinical, echocardiographic and biochemical variables to predict SCD in a consecutive cohort of patients with heart failure (HF) due to systolic dysfunction. Methods: A cohort of 494 patients with established HF had baseline echocardiographic and NT-proBNP measurements and were followed for 942 ± 323 days. Results: Fifty patients suffered SCD. Independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
5
33
0
Order By: Relevance
“…On the contrary, LV mass, IVS, and LA size were significantly larger in the obese group. Furthermore, cardiac output was significantly increased in the obese group, in agreement with hyperdynamic circulation [9][10][11]. Structural parameters such as the systolic and diastolic volumes and diameters were all significantly larger than those of the controls, in accordance with the literature [13,14].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the contrary, LV mass, IVS, and LA size were significantly larger in the obese group. Furthermore, cardiac output was significantly increased in the obese group, in agreement with hyperdynamic circulation [9][10][11]. Structural parameters such as the systolic and diastolic volumes and diameters were all significantly larger than those of the controls, in accordance with the literature [13,14].…”
Section: Discussionsupporting
confidence: 87%
“…Morbid obesity is associated with hyperdynamic circulation and hypervolemia, leading to elevated left ventricle (LV) filling pressures [9][10][11]. The latter often leads to left atrium (LA) enlargement, as one of the earliest manifestations of left ventricle diastolic dysfunction (LVDD).…”
Section: Introductionmentioning
confidence: 99%
“…LA EF was also significantly decreased; that can be explained by the increase in V min and similarity in V max . Although increased V max is an important prognostic predictor in various cardiac diseases (1)(2)(3)12,32,33), evaluating V min and LA EF might aid in detecting early, subclinical LA filling impairment. We demonstrated that LA strain and strain rate were significantly different between the subclinical myocardial scar group and the control group.…”
Section: La Parametersmentioning
confidence: 99%
“…Numerous studies have examined the value of natriuretic peptides to assess the prognosis of HF [33][34][35][36] , most of them performed in the emergency room or in patients with acute decompensated HF requiring hospitalization. Few of the studies focus on stable chronic HF [37,38] .…”
Section: Previous Studiesmentioning
confidence: 99%